Genetic architecture and clinical features of Tourette syndrome in a child and adolescent cohort: an explorative clinical exome-based study - Saia, Federica; Mirabella, Federica; Longhitano, Andrea; Maugeri, Nicoletta; Barone, Rita; Rizzo, Renata (Frontiers in Psychiatry, 2026)
BackgroundTourette Syndrome (TS) is a neurodevelopmental disorder with a complex genetic architecture, involving both rare high-impact variants and polygenic contributions. While several risk genes have been identified by whole-exome sequencing (WES), the relationship between genetic variants and clinical phenotype in TS patients remains insufficiently characterized.MethodsWe conducted an explorative clinical exome-based study in a cohort of 80 children and adolescents with TS (mean age 12.8 years; male:female = 70:10). Variants were classified as potentially causative (PC-Vs), variants of uncertain significance (VUS), or non-causative (NC-Vs) according to ACMG guidelines for variant evaluation and curated databases. Clinical assessment included tic severity through Yale Global Tic Severity Scale (YGTSS), cognitive testing, dysmorphic features, comorbid conditions, EEG and brain MRI analyses. Group comparisons were statistically performed to evaluate associations between genetic findings and phenotypic features.ResultsOut of the 80 patients, 11 (13.7%) carried PC-Vs, 29 (36.3%) VUS, and 40 (50%) NC-Vs. Patients with PC-Vs exhibited significantly higher tic severity (mean YGTSS 28 ± 8.2) and lower IQ (67.6 ± 31.0) compared with VUS (YGTSS 24.2 ± 7.7; IQ 90.8 ± 23.1) and NC-Vs (YGTSS 18.5 ± 7.0; IQ 86.4 ± 20.3) (p < 0.05). Conversely, positive family history of tics was more frequent in the NC-V group (55%) than in PC-Vs (27.3%) or VUS (27.6%) (p = 0.044). Potential causative variants included de novo or inherited mutations in genes implicated in synaptic transmission (PNKD, SLC6A1), ion channels (CACNA1D), chromatin remodeling (BRPF1, KMT2C, SMARCA2), and pleiotropic neurodevelopmental pathways (PTEN, RERE).ConclusionThese findings support a dual model of genetic susceptibility in TS, where rare, high-impact exomic variants may contribute to more severe tics, cognitive impairment, and syndromic presentations, whereas polygenic inheritance mostly occurs in familial and milder forms. Incorporating exome sequencing into diagnostic workflows may enhance etiological classification and inform precision-medicine strategies for TS.